THE IMPACT OF SOCIAL MEDIA AND TECHNOLOGY ADDICTION ON MENTAL HEALTH - Yoʻldasheva Khidoyatkhon Ozodbek qizi; Yaqubjonova Ro‘zixon Mirkomil qizi (Ustozlar uchun, 2025)
Abstract: In today’s digital age, the use of social media and technology has become an integral part of daily life. While these advancements offer many benefits, such as instant communication and access to information, they also pose serious risks when overused. This article explores the psychological effects of addiction to social media and technology, emphasizing the importance of balance in digital consumption for the sake of mental well-being.